Analisis Indikator (BOR, AVLOS,TOI dan BTO) Pada Ruang Anak Dalam Peningkatan Pelayanan Kesehatan - Nina Rahmadiliyani; Ramadhan Dwi Nugrohoi; Ermas Estiyana (HB PRESS, 2020)
One problem in hospitals is the low efficiency of the use of beds (TT). This study aims to determine the analysis of indicators (BOR, AVLOS, TOI and BTO) at the child’s room in improving health services at the BLUD RSU Ratu Zalecha Martapura in 2018. This study uses descriptive research methods with qualitative and quantitative approaches. The variables used in this study were inpatient daily census in child’s rooms, BOR, AVLOS, TOI and BTO and Barber Johnson charts, the research instruments used interviews and observation. This study uses triangulation data analysis techniques. Based on the overall results of the research on the efficiency of the use of beds in child’s rooms at BLUD RSU Ratu Zalecha Martapura in 2018 with a BOR value of 69%, AVLOS which was 3.3 days, TOI 1.47 days and BTO was 75.91 times. Barber Johnson's graphic in the child’s room at BLUD RSU Ratu Zalecha Martapura in 2018 has not yet fulfilled one intersection of four.